The Fund's Capacity Development Strategy : Better Policies Through Stronger Institutions. (Policy Papers; Policy Paper, 2013)
This supplement provides background information on various aspects of capacity development (CD) for the main Board paper, The Fund's Capacity Development Strategy-Better Policies through Stronger Institutions. It is divided into nine notes or sections, each focused on a different topic covered in the main paper. Section A explores the importance of institutions for growth, and the role the Fund can play in building institutions. Section B presents stylized facts about how the landscape for CD has changed since the late 1990s. Section C discusses the difficulties of analyzing CD data because of measurement issues. Section D provides a longer-term perspective on how Fund CD has responded to member needs. Section E contains information on previous efforts to prioritize CD, assesses Regional Strategy Notes (RSNs) and country pages, and suggests ways to strengthen RSNs, including by using the Fund's surveillance products. Section F compares the technical assistance (TA) funding model proposed in the 2011.